Study of Overall Morphology and Particle-size Distribution of Spray Field in Gas–liquid Mixed Snow-makers - Hu Hengxiang; Liu Bin; Bi Lisen; Zeng Tao; Li Jiawei (Zhileng xuebao)
Since the Beijing Winter Olympic Games, the domestic ice and snow industry has grown rapidly, driven particularly by artificial snow parks with higher requirements in terms of both the quantity and the quality of artificial snow. This research showed that the quality of artificial snow was closely related to the droplet size distribution in the spray field. The droplet size distribution was affected by droplet collision, polymerization, and separation, as well as the nozzle distribution of the artificial snow-making system. Therefore, PIV and particle sizing systems were used to measure the overall morphology and droplet size distribution of the spray field generated by atomization of the gas-liquid mixed artificial snow-making system to study the effects of the gas-liquid mass ratio (gglr) and nozzle spacing on the droplet size distribution of the spray field. Our results showed that with an increase in gglr, the overall morphology of the spray field exhibited an inward shrinking trend, and the minimum average droplet size occurred below the nozzles. When gglr was constant, the interference between the two nozzles increased with a decrease in nozzle spacing, and the average droplet diameter increased with an increase in the axial distance, presenting an M-shaped distribution with a change in the radial distance.